Public debt and growth: An assessment of key findings on causality and thresholds - Michael Ash; Deepankar Basu; Arindrajit Dube (University of Massachusetts, Department of Economics, 2017)
We provide a comprehensive assessment of the relationship between public debt and GDP growth in the postwar advanced economies. We use the timing of changes in public debt and growth to account for endogeneity, and find little evidence of a negative relationship. Semi-parametric estimates do not indicate any threshold effects. Finally, we reconcile our results with four recent, influential papers that found a substantial negative relationship, especially when public debt exceeds 90 percent of GDP. These earlier results appear to derive mostly from peculiar parametric specifications of nonlinearities, or use of small samples which amplify the influence of outliers.
Keywords: E00; E6; H6; C82; 330; public debt; growth